Analyzing the effects of Covid-19 pandemic on Turkish women workers in clothing sector - Akşit Aylin; Kanat Seher (AUTEX Research Journal)
Covid-19 pandemic, which has negatively affected all sectors and life, has also negatively influenced the clothing sector, which possesses a global supply chain. Within the clothing sector, which is a labor-intensive sector, mostly women workers are employed. Women workers’ issues, who already face work–life balance and occupational segregation problems in their work lives, have also been increased with the pandemic. In this context, this research aims to analyze the effects of Covid-19 pandemic on women workers in clothing sector. In accordance with the aim of the research, a survey is conducted on women workers, who are employed in Türkiye’s provinces, where clothing sector intensively operates. The obtained results are analyzed statistically and suggestions are made to the clothing enterprises on the basis of these results. According to the obtained results, Turkish women clothing workers, who participated in the survey, indicated that the increases that occurred in their physical and psychological problems are the most important issues that they faced during the Covid-19 pandemic. Besides, participants’ emotional behaviors, concerns, anxieties, hopelessness, sleeping issues, anger, and rages also increased.